SAP ASSESSMENT USING COBIT 2019 AND ITIL FOR SYSTEM IMPROVEMENT AND STRATEGIC DECISION SUPPORT (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
The increasing reliance on Information Technology (IT) for enhancing business performance has led organizations to adopt structured governance and service management frameworks. This study evaluates the IT governance implementation at PT. Natural Indococonut Organik—an organic coconut enterprise that relies on SAP as its core enterprise system. Using the COBIT 2019 and ITIL V.3 frameworks, the study assesses IT process capability, service management maturity, and alignment with best practices. A qualitative descriptive approach was applied through three structured interviews with IT personnel. The first interview used COBIT 2019 Design Factors to identify priority processes: APO12 (Managed Risk), DSS01 (Managed Operations), and MEA03 (Managed Compliance). The second assessed these processes’ capability levels, revealing gaps below the target level (Level 4): APO12 at 33%, DSS01 at 75%, and MEA03 at 12.5%. The third interview applied the ITIL Self-Assessment to evaluate the service desk, with results indicating partial achievement and an overall maturity near Level 2. Key deficiencies were found in risk management, compliance oversight, operational consistency, and user feedback mechanisms—areas critical to supporting SAP effectively. Findings are categorized into design, evaluation, and improvement domains, demonstrating how governance analysis contributes to enhancing enterprise information systems. Strengthening SAP-related risk controls, service procedures, and user engagement processes is essential to elevate governance maturity and system performance
Keywords: COBIT 2019; ITILv3; IT Governance; IT Service Management